The efficiency evaluation of the endurance development methodology fo middle-distance and long-distance runners with account of lactate level monitoring - Sheplyakov, A. S.; Amelchenko, I. A.; Belogurov, V. A. (6th International Scientific Conference "Anthropological and teo-anthropological viewson physical activity from the time of Constantine theGreat to moderntimes". Book of proceedings., 2019)
The article deals with implementation phases and the content of methodology of combining aerobic and anaerobic-oriented means at the training exercises of track and field athletics. The findings of the time indices of covering the fractions of distance in the training days during the whole preparation period with loads at the aerobic threshold level have been presented. The feasibility of the tested methodology of using aerobic running loads in the training process of track athletes with account of monitoring the lactate level has been demonstrated.